W Band Imaging System Using Linear Sparse Periodic Antenna Array and Compressive Sensing for Personnel Screening - Shaoqing Hu; Chao Shu; Yasir Alfadhl; Xiaodong Chen (IEEE Access, 2019)
This paper presents our study on a W band imaging system consisting of a linear sparse periodic antenna array (SPA) with only 10 transmitting (Tx) and 10 receiving (Rx) elements in simulation and experiment for the purpose of personnel screening. We have devised a simplified and low cost experimental set-up using only 1 Tx and 1 Rx channels located on two scanning tracks separated by a distance to verify the proposed multi-static array imaging scheme. The simulation has taken account of the effects of track separation and measured antenna patterns. The simulation and experiment correlate quite well, indicating a resolution of about 7 mm at 1.3 m distance. Furthermore, based on the experimental data, we have investigated the compressive sensing (CS) image reconstruction as an approach for further reducing the sampling points in such a multi-static array imaging system. It is shown that using a discrete SPA-CS imaging algorithm, the images can be successfully reconstructed with the data as few as 30% of that used in the traditional holographic/synthetic aperture radar (SAR) imaging algorithm. Therefore, the CS image reconstruction is proved to be feasible for building a low-cost and fast millimeter wave imaging system.